Transforming the Event Industry: The Role of AR, VR, and Emerging Technologies in Event Management - Bisht, Ajay; Bhatt, Pradeep (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2025)
The event management industry is transforming due to the  rapid integration of emerging technologies such as Augmented  Reality (AR) and Virtual Reality (VR). These innovations are  significantly impacting various operational aspects, including  strategic planning, attendee engagement, and service delivery.  This study aims to explore the evolving role of AR and VR  in enhancing event experiences and improving decision making efficiency. Employing a mixed-methods approach,  the research combines quantitative surveys of event planners,  observational studies comparing traditional and tech integrated events, and qualitative interviews with attendees  and key stakeholders. The findings indicate substantial  improvements in event outcomes, including a 30% increase  in strategic planning effectiveness, a 17.5% boost in attendee  engagement, and a 28.9% enhancement in decision-making  processes. The results underscore the potential of immersive  technologies to revolutionize event execution and knowledge  dissemination. The study contributes to the growing body  of literature on technological innovations in events, offering  practical implications for event professionals seeking to  leverage AR and VR for more immersive and efficient event  experiences.
Keywords: Event Technology; Event Planning and Management; Augmented Reality (AR); Virtual Reality (VR); Virtual Events